English Language Needs Analysis for Electrical Engineering Students: A Case Study at Tulungagung University - Mochamad (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2026)
The need for English language proficiency in engineering is increasing along with industrial globalization, technological developments, and the dominance of English-language scientific literature. This study aims to analyze the English language needs of Electrical Engineering students at Tulungagung University as a basis for developing a contextual, needs-based English for Specific Purposes (ESP) curriculum. The study used a qualitative approach with a case study design. Data were collected through questionnaires, semi-structured interviews, and curriculum document analysis with students, lecturers, and industry stakeholders. The needs analysis refers to the target needs and learning needs framework as proposed by Hutchinson and Waters (1987) and Dudley-Evans and St John (1998). The results show that students require more skills in reading technical texts, understanding equipment manuals, writing lab reports, and oral communication skills for project presentations and technical discussions. In addition, there is a gap between general English material and the demands of academic and professional competencies in engineering. These findings align with global research that emphasizes the importance of a needs-based approach in ESP development (Basturkmen, 2010; Hyland, 2006). Therefore, this study recommends the development of a needs-based syllabus integrated with the context of Electrical Engineering and collaboration with the industrial world to enhance learning relevance. This research contributes to enriching ESP studies in the engineering field in the context of Indonesian higher education.